Effect of Polyvalent Ions in the Formation of Ionic-Liquid-Based Aqueous Biphasic Systems - Kurnia, Kiki A.
Two main approaches were combined aiming at evaluating the impact of polyvalent salt cations on the formation of ionic-liquid-based aqueous biphasic systems (ABS): (1) experimental determination of a large array of ternary phase diagrams composed of sodium-, magnesium-, and aluminum-based salts with 1-butyl-3-methylimidazolium-based ionic liquids and (ii) determination of the ions speciation in each of these systems. The results here reported show, for the first time, that the phase behavior of ionic-liquid-based aqueous biphasic systems is not only dominated by the ability of the strong and \"free\" salting-out ions to interact with water creating thus hydration complexes but also a result of the interactions occurring between the different ions and, particularly, on their speciation in aqueous solutions. The gathered data indicate that the higher the salt ion valence, the more complex is its speciation with a number of different species in aqueous media present. Further results based on NMR spectroscopy and a proper analysis of the pH influence clearly demonstrated the impact of ion speciation through the phase separation and ABS formation.